IMPLEMENTASI SUPERVISI AKADEMIK KEPALA MADRASAH DALAM MENINGKATKAN MUTU PENDIDIK DI MTs SA MIFTAHUL HIKMAH PARENGAN TUBAN - Fatimah, Siti; Rosyidah, Irma (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2021)
Activities supervision Academic are very necessary for educators, because the driving and determining factors for education outcomes are strongly influenced by the quality of the educator. Therefore, periodically the principal of madrasah needs to carry out supervision activities. The principal’s duty as a supervisor is to supervise the work done by his educators. One of the supervision activities that need to be carried out by the head of madrasah is to carry out academic supervision. Through academic supervision, it is expected that the academic quality carried out by educators will incerease and have quality. Therefore, the principal of the madrasah must be able to know the achievements of his educators in carrying out the process of teaching and learning activities.The purpose of this study was to describe the implementation of academic supervision by the principal in improving the quality of teachers at MTs SA Miftahul Hikmah Parengan Tuban. The research that the authors do is included in qualitative research. In collecting data, the write used interview, observation and documentation methods. Research subjects consisted of the head madrasah and the entire teacher council in MTs SA Miftahul Hikmah Parengan Tuban.The results of the study show that the implementation of academic supervision at MTs SA Miftahul Hikmah Parengan Tuban has been running quite well, it can be seen that the implementation of ecademic supervison techiques is carried out by the principal in improving the quality educators. Supervision is carried out once every semester, there are two supervision carried out by the principal, namely academic supervision and administrative supervision. Where these two things can support in improving the quality of educator, as for the support in improving the quality of educators. Namely in the form of MGMP, education and training, seminars and workshops